2009
DOI: 10.1002/chem.200901427
|View full text |Cite
|
Sign up to set email alerts
|

Acid‐, Water‐ and High‐Temperature‐Stable Ruthenium Complexes for the Total Catalytic Deoxygenation of Glycerol to Propane

Abstract: The ruthenium aqua complexes [Ru(H(2)O)(2)(bipy)(2)](OTf)(2), [cis-Ru(6,6'-Cl(2)-bipy)(2)(OH(2))(2)](OTf)(2), [Ru(H(2)O)(2)(phen)(2)](OTf)(2), [Ru(H(2)O)(3)(2,2':6',2''-terpy)](OTf)(2) and [Ru(H(2)O)(3)(Phterpy)](OTf)(2) (bipy = 2,2'-bipyridine; OTf(-) = triflate; phen = phenanthroline; terpy = terpyridine; Phterpy = 4'-phenyl-2,2':6',2''-terpyridine) are water- and acid-stable catalysts for the hydrogenation of aldehydes and ketones in sulfolane solution. In the presence of HOS(O)(2)CF(3) (triflic acid) as a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
89
0
3

Year Published

2012
2012
2020
2020

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 69 publications
(97 citation statements)
references
References 60 publications
5
89
0
3
Order By: Relevance
“…Given that hydrogenolysis of FFR (a trace of 2-MF) was observed in the reaction of FFR with H 2 (51 atm) catalyzed by cis-[Ru (6, (1) has been reported to be 135˚C), [44] as well as in solvents that would preclude formation of acetal and/or ether by-product(s). Reaction of FFR with H 2 (51 atm) in the presence of 1 mol% of 1 at 130 C in ethanol for 4 h proceeded to 100% FFR conversion and furnished a mixture of products (Table 3, entry 8), including FFA (17% yield), 2-MF (20% yield), and 2-(diethoxymethyl) furan (furfural diethyl acetal, 14% yield).…”
Section: Resultsmentioning
confidence: 97%
“…Given that hydrogenolysis of FFR (a trace of 2-MF) was observed in the reaction of FFR with H 2 (51 atm) catalyzed by cis-[Ru (6, (1) has been reported to be 135˚C), [44] as well as in solvents that would preclude formation of acetal and/or ether by-product(s). Reaction of FFR with H 2 (51 atm) in the presence of 1 mol% of 1 at 130 C in ethanol for 4 h proceeded to 100% FFR conversion and furnished a mixture of products (Table 3, entry 8), including FFA (17% yield), 2-MF (20% yield), and 2-(diethoxymethyl) furan (furfural diethyl acetal, 14% yield).…”
Section: Resultsmentioning
confidence: 97%
“…sulfuric acid) were added to improve catalytic conversions. There are also reports [46][47][48][49][50][51][52] on the use of homogeneous ruthenium catalysts in combination with triflic acid (HOTf) and sulfolane as the solvent for the selective hydrodeoxygenation of a secondary alcohol in the presence of a primary alcohol. For example, Schlaf et al [51] reported the production of 1-propanol from 6 using [{Cp*Ru(CO) 2 While preparing this manuscript, Dumesic et al [44] reported hydrodeoxygenation reactions of various diols and triols using bimetallic Rh-ReO x catalysts on carbon supports.…”
Section: 6-hexanediolmentioning
confidence: 99%
“…Therefore over-hydrogenolysis to propanols and even propane can proceed over the catalysts that can work by the dehydration + hydrogenation route. Homogeneous Ru and Ir complexes combined with external acid are typical catalysts for production of propanols or propane from glycerol [10,11] and 1,2-PrD [12][13][14]. In contrast, under more basic conditions over heterogeneous metal catalysts, the dehydrogenation + dehydration + hydrogenation route is preferred to the dehydration + hydrogenation route.…”
Section: Conventional Hydrogenolysis Of Glycerol and Tetrahydrofurfurmentioning
confidence: 99%